Social Media-Based Political Campaign Strategies and the Impact of Filter Bubbles and Echo Chambers on the Electability of Presidential Candidates in the 2024 Election in Indonesia. - Danial Dengo Ate; Muhammad Ridwan; Samsul Ode (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This research investigates how filter bubbles and echo chambers on Facebook and Instagram shape Indonesia's 2024 presidential election campaign. The research addresses the issue of social media algorithms amplifying selective exposure, which can deepen political polarization and limit voters' access to diverse viewpoints. This research aims to analyze campaign strategies in a digital environment, assess their influence on candidate electability among young voters, and examine the role of algorithms in shaping political information consumption. Using a qualitative approach, this research employs thematic content analysis on campaign posts, public comments, and screenshot data from Facebook profiles, supported by sentiment analysis. The results show that campaign teams strategically leveraged social media algorithms to customize messages, reinforce confirmation bias and amplify ideological divisions. Sentiment analysis of 100 online comments about the free lunch program showed that 39% were negative, 35.4% neutral, and only 25.6% positive, indicating prevalent skepticism. This research concludes that algorithm-based campaign strategies significantly impact messaging and voter perceptions, especially among digitally active youth, highlighting the need for more transparent algorithms and media literacy to support healthier democratic engagement.